2021
DOI: 10.1186/s12902-021-00786-7
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D supplementation improve ovarian reserve in women with diminished ovarian reserve and vitamin D deficiency: a before-and-after intervention study

Abstract: Objective Evaluation of vitamin D supplementation on ovarian reserve in women with diminished ovarian reserve and vitamin D deficiency. Methods The study is a before-and-after intervention study that was performed on women with diminished ovarian reserve referred to Shahid Mofteh Clinic in Yasuj, Iran. Eligible women were prescribed vitamin D tablets at a dose of 50,000 units weekly for up to 3 months. Serum levels of vitamin D and AMH were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Aramesh et al did a before-and-after intervention study on 51 women with DOR (AMH <1 ng/ml) and vit D deficiency (Vit D less than 20 ng/ml) without any control group. 13 The study showed that serum levels of both AMH and Vit D increased significantly (p<0.05) after an oral dose of vitamin D 50,000 IU per week for 3 months. Before the treatment the median serum vitamin D level was 12.1 ng/ml and after the treatment it increased to 26 ng/mL which was statistically significant (p<0.001).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Aramesh et al did a before-and-after intervention study on 51 women with DOR (AMH <1 ng/ml) and vit D deficiency (Vit D less than 20 ng/ml) without any control group. 13 The study showed that serum levels of both AMH and Vit D increased significantly (p<0.05) after an oral dose of vitamin D 50,000 IU per week for 3 months. Before the treatment the median serum vitamin D level was 12.1 ng/ml and after the treatment it increased to 26 ng/mL which was statistically significant (p<0.001).…”
Section: Resultsmentioning
confidence: 88%
“…Our women were in their thirties on average comparable to the studies on women with DOR. 9,13,14 Middle and higher socioeconomic status and urban living provide easier access to health care as well as better control over reproductive health in comparison to people living in lower socioeconomic condition or rural areas. In this study, maximum participants had household monthly income over 10,000 taka per month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moridi's study concluded that there is no correlation in most studies between blood levels of vitamin D and AMH. On the other hand, the study of Aramesh et al in Iran [ 43 ] found an important correlation between the number of eggs and the administration of vitamin D supplementation, which supported the possibility of the effect of vitamin D on increasing the expression of AMH through the effect of a promoter in the AMH gene, which led them to deduce that levels of AMH may be increased by vitamin D without affecting the number of follicles (and this is consistent with our result for follicles number). Other research has linked decreased vitamin D status with increased AMH levels, which causes an increase in large follicles production and the number of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…in Chinese, not shown) [ 1 , 2 ]. The main reasons for DOR include genetics, aging, stress, endometriosis, reproductive endocrine disorders, chemotherapy and radiotherapy, excessive drinking, autoimmune diseases, chemical toxins, ovarian induction agents, certain systemic diseases, previous mumps infection, and some unclear etiologies [ 3 ]. Although there is no generally accepted definition of DOR, it has been described as a pathophysiological ovarian state characterized by poor fertility outcome, poor ovarian response, and an abnormal ovarian reserve [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%